The United States and a Changing Middle East - NCAFP (American foreign policy interests, 2012)
Expert presenters discuss and debate the Arab Spring; the "Third Arab Way"; Islam, the Muslim Brotherhood, and the role of religion; the U.S. presence or lack of it in the Middle East; how Americans' worldviews and geographic circumstances affect U.S. foreign policy in the region and the world; the conflagration that is Syria and UN attempts at mediation/resolution; U.S. and regional responses to the nuclear and hegemonic ambitions of Iran; Iraq and Turkey as models of evolution toward regime change through the ballot box; the changing Russian presence; and the five fundamental issues involved in the Israeli-Palestinian conflict.